2005
DOI: 10.1103/physrevlett.94.111302
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Preclassical Solutions in Bianchi I Loop Quantum Cosmology

Abstract: Loop quantum cosmology, the symmetry reduction of quantum geometry for the study of various cosmological situations, leads to a difference equation for its quantum evolution equation. To ensure that solutions of this equation act in the expected classical manner far from singularities, additional restrictions are imposed on the solution. In this paper, we consider the Bianchi I model, both the vacuum case and the addition of a cosmological constant, and show using generating function techniques that only the z… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 18 publications
1
61
0
Order By: Relevance
“…In particular, V µ+δ,τ − V µ−δ,τ = 0 when µ = 0, and V µ,τ +δ − V µ,τ −δ = 0 when τ = 0. This situation arises in previous work in loop quantum cosmology, such as the isotropic [4] and the Bianchi I and IX models [8,9,10]. If we write the wave function Ψ solving the Hamiltonian constraint as a sum of eigenstates…”
Section: The Schwarzschild Interior In Loop Quantum Cosmologymentioning
confidence: 99%
“…In particular, V µ+δ,τ − V µ−δ,τ = 0 when µ = 0, and V µ,τ +δ − V µ,τ −δ = 0 when τ = 0. This situation arises in previous work in loop quantum cosmology, such as the isotropic [4] and the Bianchi I and IX models [8,9,10]. If we write the wave function Ψ solving the Hamiltonian constraint as a sum of eigenstates…”
Section: The Schwarzschild Interior In Loop Quantum Cosmologymentioning
confidence: 99%
“…Many studies have already been devoted to Bianchi-I LQC [97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117]. In particular, it was shown that the bounce prediction is robust.…”
Section: Further Developmentsmentioning
confidence: 99%
“…In such models, limitations similar to that of a cosmological constant have been observed as possible instabilities of solutions in classical regions or the lack of a sufficient number of semiclassical states [27,28,29]. For the partial difference equations of anisotropic models in loop quantum cosmology, stability issues can be much more severe than in isotropic models and thus lead to further consistency tests which might help to restrict possible quantization freedom (see, e.g., [30]).…”
Section: Introductionmentioning
confidence: 99%